Brainstem tumors in children: a monocentric series in the light of genetic and bio-molecular progress in pediatric neuro-oncology - Boukaka, Rel Gerald; Beuriat, Pierre-Aurélien; Di Rocco, Federico; Vasiljevic, Alexandre; Szathmari, Alexandru; Mottolese, Carmine (Frontiers in Pediatrics, 2023)
Introduction: Brainstem tumors represent a challenge. Their management and prognosis vary according to anatomopathological findings and genetic and bio-molecular fingerprints. We present our experience with pediatric brainstem tumors.All patients admitted for a brainstem tumor at the Pediatric Neurosurgical Unit at Hôpital Femme Mère Enfant hospital between January 1997 and December 2019 were considered. Patients data were obtained through a retrospective review of the medical records; follow-up was from the last outpatient consultation.Results: One hundred and twelve patients were included. Eighty-five patients (75.9%) had open surgery or stereotactic biopsy. Thirty-five patients were treated for hydrocephalus. Sixty-six received an adjuvant treatment. Several protocols were adopted according to the SFOP and SIOP during this time period. The overall survival rate was 45% with a median follow-up of five years (range 1 to 18 year). However, the survival rate was very different between the diffuse intrinsic pontine gliomas (DIPG) and the others tumor types. If we exclude the DIPG (59 patients), of which only 1 was alive at 3 years, the survival rate was 90.6% (only 5 deaths over 53 patients) with a median follow up of 5 years.Our series confirms that benign tumors of the brainstem have a good survival when treated with surgical removal +/-adjuvant therapy. Diffuse pontine gliomas continue to have a dismal prognosis. Individualized treatment based on molecular fingerprints may help to select the best adjuvant therapy and hence potentially improve survival.